Vlačenje ploha v Pliberku in okolici - Križnar, Naško (Traditiones (Ljubljana), 1999)
Dragging a plank is un urban Shrovetide custom in which a group of boys maskedas loggers sells pieces of pine trunk to unmarried young women. The purpose of this visual research was to describe and analyze the custom and to discover possible connections within the broader geographical area. This research is part of a joint research project entitled Vlačenje ploha v Pliberku in okolici (Dragging a Plank in Bleiburg and its Vicinity). The development and expansion of theis custom in nearby Slovene villages is desribed by martina Piko in her article on page 369
Keywords: ethnology; etnologija